(untitled) (Journal of Engineering, 2006)
A one-dimensional finite difference model for the simultaneous movement of light nonaqueous phase liquid (LNAPL) and water through unsaturated-saturated zone of the soil in a three fluid phase system with air assumed constant at atmospheric pressure is developed. The flow equations described the motion of light non-aqueous phase liquid and water are cast in terms of the wetting and non-wetting fluid pressure heads respectively. The finite difference equations are solved fully implicitly using Newton-Raphson iteration scheme. The present numerical results are compared with results of Kaluarachchi and Parker (1989) and there is a good agreement between them. The present model can be used to simulate various transport problems in a good manner. Results proved that the maximum LNAPL saturation occurred below the source of the contaminant during LNAPL infiltration. During redistribution, the LNAPL saturation had a maximum value at the advancing of the LNAPL infiltration front.